Debris‐Flood Hazard Assessments in Steep Streams. Issue 4 (11th April 2022) - Jakob, Matthias; Davidson, Sarah; Bullard, Gemma; Busslinger, Matthias; Collier‐Pandya, Beatrice; Grover, Patrick; Lau, Carie‐Ann
Abstract: Debris floods most commonly occur in steep mountain channels and on their alluvial fans but can also occur on small gravel bed rivers with watershed areas up to several hundred square kilometers. This became obvious during July 2021 and November 2021 debris floods in northwestern Germany and southwestern British Columbia, Canada. We subdivide debris floods into three categories: those triggered by a supra‐critical bed shear stress ratio, form by dilution from debris flows, and resulting from outbreak floods. This trichotomy challenges traditional hazard assessments; debris floods classify as a fluvial process, yet their destructive mechanics are difficult to characterize. Key hazards interact spatially and temporally in debris floods: inundation, scour, sediment transport and deposition and bank erosion. We describe approaches to quantify hazards by systematically accounting for these processes and introduce a novel approach for hazard quantification and mapping in which flow velocity, depth, and presumed fluid density are combined with the annual event frequency for all event scenarios. The derivative "composite hazard maps" are equally valid for debris floods and debris flows. Isolines of bank erosion based on a probabilistic analysis of a physically based model are added to capture the potential of debris floods to abruptly widen their channels. Substantial challenges remain, specifically in the reliable prediction of sediment transport and progressive bank erosion. Our intention is to homogenize debris‐flood hazard assessments and especially mapping methodologies. This could allow for systematic integration with landuse policies assuring consistency among approaches executed by practitioners acting in this field. Plain Language Summary: Debris floods can be highly destructive. We provide a comprehensive methodology to assess debris‐flood hazards with the goal of developing a consistent approach, allowing for better input to quantitative risk assessments and the selection of appropriate mitigation measures. We suggest a method for debris‐flood mapping that combines the recurrence interval of various debris flood scenarios with their impact force and bank erosion to support a multi‐faceted hazard assessment. Key Points: Debris flood assessments are under‐researched and poorly constrained. This contribution attempts to rectify that situation Beyond debris flood inundation, this contribution outlines methods for sediment bulking, sediment transport, and bank erosion A new method for hazard mapping is proposed based on impact force and event frequency. This allows direct comparison of study sites